The Effect of Change Management and Knowledge Management on Organizational Performance: The Mediating Effect of Innovation Capability - Sania, Encep; Siregar, Khairani Ratnasari; Ahmad, Jamilah (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study investigates how change management and knowledge management affect organizational performance through the mediating influence of innovation capability in an Indonesian IT managed services provider navigating digital transformation challenges. The main objective of this research is to investigate the direct and indirect effects of change management and knowledge management on organizational performance through the mediating influence of innovation capability. A quantitative explanatory approach was employed, with data collected via structured questionnaires from 120 employees actively involved in relevant processes at the company. Variance-based structural equation modeling using SmartPLS software analyzed the relationships among the constructs. The results indicate that knowledge management has a strong positive effect on innovation capability, which in turn significantly influences organizational performance. Innovation capability partially mediates the relationship between knowledge management and organizational performance. In contrast, change management shows no significant effect on innovation capability or its mediation role, though it directly contributes to organizational performance. The model explains moderate variance in both innovation capability and organizational performance. In conclusion, knowledge management primarily drives innovation-led performance in this digital service context, whereas change management supports performance through operational alignment rather than creative mechanisms.